2011
DOI: 10.1080/03630242.2011.627091
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes of Human Papillomavirus Vaccine, and Intention to Obtain Vaccine Among Korean Female Undergraduate Students

Abstract: The purpose of this study was to examine knowledge about the human papillomavirus and attitudes toward human papillomavirus and human papillomavirus vaccination among Korean female undergraduate students. Moreover, this study sought to identify factors associated with intention to obtain the human papillomavirus vaccine. A cross-sectional study was conducted with 297 Korean female undergraduate students. Data were collected using a self-administered questionnaire. Collected data were analyzed with descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 37 publications
6
44
0
Order By: Relevance
“…This finding was consistent with those from a previous study on a peer health education program that reported an increase in adolescents' primary prevention knowledge about HPV (Ferrara et al, 2012). Previous studies reported that increased knowledge was associated with improved cervical cancer prevention behaviors, such as condom use, Pap tests (Saha et al, 2010), and the intent to practice cervical cancer prevention behaviors (Hsu et al, 2009;Kang & Kim, 2011). The participants in this study reported pre-intervention knowledge levels of 45.4% for the experimental group and 45.5% for the control group, neither reaching 50%.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…This finding was consistent with those from a previous study on a peer health education program that reported an increase in adolescents' primary prevention knowledge about HPV (Ferrara et al, 2012). Previous studies reported that increased knowledge was associated with improved cervical cancer prevention behaviors, such as condom use, Pap tests (Saha et al, 2010), and the intent to practice cervical cancer prevention behaviors (Hsu et al, 2009;Kang & Kim, 2011). The participants in this study reported pre-intervention knowledge levels of 45.4% for the experimental group and 45.5% for the control group, neither reaching 50%.…”
Section: Discussionmentioning
confidence: 56%
“…However, Korean women in their 20s and 30s are relatively less aware than women in their 40s and 50s of cervical cancer's severity and the importance of early check-ups for cervical cancer, placing these age groups in a blind spot for cervical cancer check-ups (Han, 2011). Previous Korean studies have demonstrated low rates of condom use (Han, 2011;Kim, 2009), Pap testing (Kim, 2009), and HPV vaccinations (Kang & Moneyham, 2010;Kang & Kim, 2011) among Korean female college students.…”
Section: 연구의 필요성mentioning
confidence: 99%
See 3 more Smart Citations